P311 TAKOTSUBO CARDIOMYOPATHY RELATED TO MRNA SARS–COV2 VACCINE. (18th May 2022) - Ricci, G; Citarelli, G; De Laura, D; Degennaro, L; Ligurgo, L; Sassara, M; Corriero, F; Musci, S; Desario, P; Rutigliano, D; Basso, P; Parisi, G; et al.
Abstract: 54–year–old woman with a family history of systemic sclerosis, with no significant cardiological history. She underwent anti–Covid vaccination in February and March 2021 with Spikevax (Moderna) and a booster dose (Spikevax) on 09/12/21. A few hours after this last administration, the patient presented with palpitations, asthenia, and intermittent chest tightness. In the following days, because of dyspnea for mild exertion, she went to the emergency department. ECG showed low QRS voltages in the peripheral leads, poor septal r wave growth and negative T waves in inferior leads and from V3 to V6. Echocardiography showed akinesia of apical and middle segments, LVEF 40%, mitral obstructive systolic anterior motion, moderate mitral regurgitation and mild pericardial effusion. In blood tests: increase in myocardiospecific enzymes and NTproBNP, modest increase in indices of inflammation. The patient was admitted to Cardiology Unit, where coronary angiography showed coronary arteries free from stenosing lesions and Takotsubo–like appearance on ventriculography. Cardiac MRI confirmed alterations in parietal kinetics, hyperintensity in the STIR sequences referable to apical and middle segments edema compatible with Takotsubo cardiomyopathy (CMT). Capillaroscopy excluded scleroderma pattern. The patient presented a progressive reduction of troponins and, the echocardiogram before discharge showed improved LV systolic function, regression of mitral obstructive systolic anterior motion with reduction of mitral regurgitation. Rare case reports of CMT after influenza vaccination [1] and a similar case to the one we described after Spikevax vaccine [2] and ChAdOx1 nCov–19 (AstraZeneca) [3] have been presented in the literature. The underlying pathophysiological mechanism appears to be related to a stress–induced systemic reaction with a predominantly adrenergic sympatho–vagal imbalance [4]. In this clinical setting, cardiac MRI can offer added value in the diagnostic process, especially to exclude post–vaccine myocarditis, which in our case seemed unlikely given the immediate onset of symptoms.